ПІДВИЩЕННЯ РЕЙТИНГУ ЖУРНАЛУ – СПІЛЬНА СУМЛІННА СПРАВА АВТОРІВ ТА РЕДАКЦІЇ (Інститут електродинаміки НАН України, Київ, 2012)
The issue of increasing the rating of the magazine "Technical Electrodynamics" was considered. Taking into account the received opportunity to significantly increase the level of "accessibility of TE to a global audience" and the responsibility that follows from this fact, specific steps for further rating improvement are outlined.